1984
DOI: 10.2307/3898822
|View full text |Cite
|
Sign up to set email alerts
|

Fire Intensity Effects on the Understory in Ponderosa Pine Forests

Abstract: The effect of fire intensity on understory vegetation on serri stands of ponderosa pine are presented. Vegetational recovery for 2 burn intensities and unburned sites were compared. The results suggest a change in the understory dominance structure foilowhrg underburning is related to the amount of duff consumed by the fire and independent of fire line intensity and flame length. A significantly greater proportion of duff was removed on high fire intensity sites (80%) than on low intensity sites (40%). However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 9 publications
1
27
0
2
Order By: Relevance
“…In P. ponderosa Dougl. (ponderosa pine) forest perennial grass cover decreased and invasive species increased as fire intensity and litter consumption increased (Armour et al 1984;Griffis et al 2001;Bataineh et al 2006;Sabo et al 2009). …”
Section: Herbaceous and Ground Cover Responsementioning
confidence: 99%
“…In P. ponderosa Dougl. (ponderosa pine) forest perennial grass cover decreased and invasive species increased as fire intensity and litter consumption increased (Armour et al 1984;Griffis et al 2001;Bataineh et al 2006;Sabo et al 2009). …”
Section: Herbaceous and Ground Cover Responsementioning
confidence: 99%
“…Rowe (1983) reported that DOB, rather than intensity, is useful in measuring plant responses following fire. Reports by Armour et al (1984) and Bidwell et al (1992) also indicated that understory vegetation response is coupled to DOB, not to fire intensity.…”
mentioning
confidence: 99%
“…In high-intensity sites, there is maximum loss of ground vegetation (Armour et al 1984), however luxuriant growth of shrubs occurs in medium and lowintensity sites (Fire Science brief 2009). Among the three burned sites of the present study similar results has been observed.…”
Section: Discussionmentioning
confidence: 99%
“…After visiting the surface burned affected forest, three sites were classified on the basis of frequency (fire event within a time period) and intensity (fire severity) of surface fire and one site as a control. The sites were categorized as high frequency and high intensity site (HFHI), high frequency and moderate intensity site (HFMI), high frequency and low intensity site (HFLI), and a control (unburned) site, after collecting the basic data of height of ground vegetation (Armour et al 1984), charcoal accumulation on ground (Turcios et al 2016), needle accumulations, fired level on tree trunks of Pine and other species (Fire Science Brief 2009), presence of olive trees (James et al 1985), coverage of bare land, number of burned species etc. The criterion has been summarized as below: a) High frequency and high intensity (HFHI) site: Characterized by low canopy coverage (22%) of ground vegetation (Fig.…”
Section: Site Selection Criterionmentioning
confidence: 99%